Colloids for Catalysts: A Concept for the Preparation of Superior Catalysts of Industrial Relevance. Issue 38 (23rd August 2018) - Quinson, Jonathan; Neumann, Sara; Wannmacher, Tanja; Kacenauskaite, Laura; Inaba, Masanori; Bucher, Jan; Bizzotto, Francesco; Simonsen, Søren B.; Theil Kuhn, Luise; Bujak, Dajana; Zana, Alessandro; Arenz, Matthias; et al.
Abstract: Compared to conventional preparation methods for supported heterogeneous catalysts, the use of colloidal nanoparticles (NPs) allows for a precise control over size, size distribution, and distribution/location of the NPs on the support. However, common colloidal syntheses have restrictions that limit their applicability for industrial catalyst preparation. We present a simple, surfactant‐free, and scalable preparation method for colloidal NPs to overcome these restrictions. We demonstrate how precious‐metal NPs are prepared in alkaline methanol, how the particle size can be tuned, and how supported catalysts are obtained. The potential of these colloids in the preparation of improved catalysts is demonstrated by two examples from heterogeneous catalysis and electrocatalysis. Abstract : The Co4Cat process is a simple method to obtain stable colloidal dispersions of precious‐metal nanoparticles in alkaline mono‐alcohols. The surfactant‐free method bears economic advantages for the preparation of supported catalysts with improved performance.